Hydrogeochemistry, Geothermometry, and Genesis of the Hot Springs in the Simao Basin in Southwestern China - Yuqi Zhang; Xun Zhou; Haisheng Liu; Mingxiao Yu; Kuo Hai; Mengru Tan; Dongxue Huo (Geofluids)
In the Simao Basin in southwest China widely occur red beds of poor permeability. Nevertheless, more than 100 springs exist in the basin, some of which are hot springs with varying temperature. Hot springs contain abundant information on hydrogeochemical processes and groundwater circulation. In this study, hydrochemical and isotopic analyses and mixed models are used to examine the sources of recharge, heat, and solutes of the hot springs to better understand the subsurface processes and formation mechanisms of different hot springs in the basin. Three types of springs are found in the Simao Basin: springs of HCO3-Na type occur in the metamorphic rocks, springs of HCO3-Ca(Mg) and Cl-HCO3-Na-Ca types in the carbonate rocks, and springs of Cl(SO4)-SO4(Cl)-HCO3-Na(Ca) type in the red beds. Data of δ2H and δ18O indicate that the hot springs in the Simao Basin are meteoric in origin. Incongruent dissolution is the dominant process affecting the chemical compositions of the spring waters. The hydrochemical constituents of the hot springs in the metamorphic rocks, carbonate rocks, and red beds are influenced by the weathering of albite and the dissolution of carbonate, gypsum, anhydrite, and halite. The geothermal waters are mixed with shallow cold waters in their ascending processes, and the mixing ratios of cold water range from 58% to 94%. Due to the effect of mixing, the reservoir temperatures (51°C-127°C) calculated with the quartz geothermometer are regarded as the minimum reservoir temperatures. More reliable reservoir temperatures (91°C-132°C) are estimated with the fixed-Al method. The following mechanisms contribute to the formation of hot springs in the Simao Basin: the groundwater receives recharge from infiltration of precipitation and undergoes deep circulation, during which groundwater is heated by heat flow and incongruently dissolves the subsurface minerals and emerges in the form of hot springs along the permeable fracture or fault zones.